1992
DOI: 10.1159/000470319
|View full text |Cite
|
Sign up to set email alerts
|

Localized Basal Ventricular Septal Hypertrophy: Prevalence, Functional and Clinical Correlates in a Population Referred for Echocardiography

Abstract: Localized hypertrophy of the basal ventricular septum was detected in 27 (0.7%) of 4,000 patients, referred for echocardiography for clinical indications, who were studied prospectively. This finding was seen primarily in older patients (mean age 66 years) without resting left ventricular outflow gradients or a family history of hypertrophic cardiomyopathy or sudden death. Although patients presented with a variety of symptoms, these were not clearly related to the septal hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…A history of hypertension was evident in 6 of the 7 subjects, whilst it was present in only 2 of the 8 patients in the Shapiro et al study. Using different definitions, later authors reported prevalence rates as high as 10% for isolated BSH [ 4 , 5 ]. Whilst the variability in prevalence likely reflects the variability in definitions used for BSH, differences in the burden of comorbid hypertension might also have contributed.…”
Section: Prevalence Of Bshmentioning
confidence: 99%
“…A history of hypertension was evident in 6 of the 7 subjects, whilst it was present in only 2 of the 8 patients in the Shapiro et al study. Using different definitions, later authors reported prevalence rates as high as 10% for isolated BSH [ 4 , 5 ]. Whilst the variability in prevalence likely reflects the variability in definitions used for BSH, differences in the burden of comorbid hypertension might also have contributed.…”
Section: Prevalence Of Bshmentioning
confidence: 99%
“…• Всем пациентам с ГКМП измерение максимальной диастолической толщины миокарда ЛЖ рекомендуется проводить во всех сегментах, от базальных до верхушки в 2D-режиме по короткой оси ЛЖ [94,149,191,193,[202][203][204].…”
Section: еок Ib (удд 4 уур с)unclassified
“…In 1992, Gardin et al . reported the finding of 27 cases of what they termed as “lower basal ventricular septal hypertrophy” (LBVSH) out of 4000 patients referred for TTE.…”
Section: Echocardiography and Localized Septal Hypertrophymentioning
confidence: 99%
“…In 1992, Gardin et al 13 reported the finding of 27 cases of what they termed as "lower basal ventricular septal hypertrophy" (LBVSH) out of 4000 patients referred for TTE. Interestingly, they excluded patients for an apparent increase in BST "due to an abnormally increased angle between the septum and aortic root."…”
Section: Echocardiography and Localized Septal Hypertrophymentioning
confidence: 99%
See 1 more Smart Citation